The abyss of time : a study in geological time and Earth history - Lyle, Paul (Lecturer in geology) (Dunedin Academic Press, 2015)
Man's fascination with time, its extent and its measurement, is Paul Lyle's starting point as he considers the relationship of deep time and the Earth's geological resources with modern consumer society.